2021
DOI: 10.21203/rs.3.rs-287787/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and prognostic features of patients with detailed RAS/BRAF-mutant colorectal cancer in Japan

Abstract: Background: RAS/BRAF V600E mutations are the most remarkable oncogenic driver mutations in colorectal cancer (CRC) and play an important role in treatment selection. No data are available regarding the clinical and prognostic features of patients with detailed RAS/BRAFV600E-mutant metastatic CRC (mCRC) in Japan.Methods: Chemotherapy-naïve patients with mCRC were included in this study between August 2018 and July 2019. Tumor samples were collected, and RAS/BRAFV600E status was investigated. RAS/BRAFV600E statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The frequency of BRAF mutation varies globally, approximately 1.1-25% [16,49,[135][136][137][138][139]. The prevalence of BRAF mutation obtained in this study was 5.6% (95% CI: 3.9-8.0), and this is conforming 14 BioMed Research International with the several existing findings, i.e., 1.1 to 5.8% in Asian studies and 5-21% in western studies [112,131,134,[140][141][142]. Another reason for these prevalence similarities could be associated with genetic homogeneity as the studies involve certain regions, and their lifestyles and diet are almost similar [143].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The frequency of BRAF mutation varies globally, approximately 1.1-25% [16,49,[135][136][137][138][139]. The prevalence of BRAF mutation obtained in this study was 5.6% (95% CI: 3.9-8.0), and this is conforming 14 BioMed Research International with the several existing findings, i.e., 1.1 to 5.8% in Asian studies and 5-21% in western studies [112,131,134,[140][141][142]. Another reason for these prevalence similarities could be associated with genetic homogeneity as the studies involve certain regions, and their lifestyles and diet are almost similar [143].…”
Section: Discussionsupporting
confidence: 88%
“…BRAF is also a member of the RAF gene subfamily that, like KRAS, performs its function in the EGFR downstream cascade, but their mutations are less frequent than the KRAS gene mutations. Among the BRAF gene, BRAFV600E mutation is the most prevailing [134], and in this present study, BRAFV600E mutation is used to examine the prevalence of BRAF gene mutation in CRC. The frequency of BRAF mutation varies globally, approximately 1.1-25% [16,49,[135][136][137][138][139].…”
Section: Discussionmentioning
confidence: 99%
“…Giannou et al showed that NRAS mutations promote colonization of the lungs by various tumor types in mouse models [31]. However, Ikoma et al investigated the prognostic features of patients with RAS mutant CRC in Japan and showed that NRAS mutant CRC tended to have a short OS [32]. The number of NRAS-mutated CRC cases was small in our cohort, and our ndings require replication in larger investigations.…”
Section: Discussionmentioning
confidence: 60%
“…MSI-high status is characterized by a frequent right-sided colon location, poorly differentiated histology, signet ring cell carcinoma or mucinous carcinoma component, and numerous infiltrating lymphocytes [15]. BRAF V600E mutation is also frequently noted in right-sided colon cancer, and patients with tumors with MSI-high status more commonly have this mutation [16]. Loss of MLH1 or MSH6 was also noted in SMARCB1-negative rhabdoid carcinoma of the colon (Table 1), and the present patient showed an MSIhigh phenotype.…”
Section: Discussionmentioning
confidence: 99%